Respon Pertumbuhan Tengkawang (Shorea pinanga Scheff) Terhadap Pemberian Pupuk Orgaik Cair (POC) di Persemaian : Response of Tengkawang Growth (Shorea pinanga Scheff) to the Application of Liquid Organic Fertilizer (LOF) in the Seedbed - Putir, Patricia Erosa; Madiyawati, Milad; Sampang, Sampang; Agatha, Hanna Ade; Meidalena, Christy (HUTAN TROPIKA, 2024)
Tengkawang (Shorea pinanga Scheff) is an endemic species from the genus Shorea that holds significant ecological and economic value, particularly in tropical regions like Indonesia. This plant is well-known for its seeds, which can be processed into valuable vegetable oil widely used in the cosmetic, food, and pharmaceutical industries. However, the existence of tengkawang trees is increasingly threatened by deforestation, illegal logging, and land-use changes, necessitating conservation efforts and optimal seedling cultivation. During the nursery stage, proper care of tengkawang seedlings is crucial to ensure healthy and ready-to-plant seedlings. One of the critical factors influencing the success of seedling cultivation is the provision of adequate nutrition. The use of liquid organic fertilizer (LOF) is an appealing alternative to enhance seedling growth as LOF contains various essential nutrients easily absorbed by plants, along with microbes that improve soil structure and accelerate organic matter decomposition. LOF is considered more environmentally friendly than chemical fertilizers, reducing the risk of soil and water contamination. This study aimed to test the application of liquid organic fertilizer in enhancing the growth of tengkawang seedlings and to evaluate the growth response to different LOF dosages in nursery conditions. The method used was a Completely Randomized Design (CRD) with four treatments and three replications. Each treatment involved five seedlings, resulting in a total of 60 tengkawang seedlings. Data analysis was conducted using Analysis of Variance (ANOVA). The results showed a 100% survival rate for tengkawang seedlings, classified as excellent. The best LOF dosage was 20 ml, which resulted in the highest growth in height and diameter. The shoot-to-root ratio was also classified as good, falling within the NPA (shoot-to-root ratio) range of 1–3. Soil analysis indicated that the soil pH was acidic, total nitrogen was moderate, organic carbon was low to moderate, and the nutrient content of phosphorus (P) and potassium (K) was very high. The application of 20 ml LOF is recommended for the propagation of tengkawang seedlings (Shorea pinanga Scheff).